Entropy for Business Failure Prediction: An Improved Prediction Model for the Construction Industry. (12th February 2014) - Bal, Jay; Cheung, Yen; Wu, Hsu-Che
Abstract : This paper examines empirically the effectiveness of entropy measures derived from information theory combined with discriminant analysis in the prediction of construction business failure. Such failure in modern complex supply chains is an extremely disruptive force, and its likelihood is a key factor in the prequalification appraisal of contractors. The work described, using financial data from the Taiwanese construction industry, extends the classical methods by applying Shannon's information theory to improve their prediction ability and provides an alternative to newer artificial-intelligence-based approaches.